Anisotropic grain growth of mullite - Rahim, Nor Fazlan (2013)
In this report, mullite ceramics with anisotropic grains were attained from a mixture containing aluminum oxide (Al2O3) and silica (SiO2) from high-energy ball milling. The effects of sintering temperature (1000oC, 1100oC, 1200oC, 1300oC, 1400oC and 1500oC) and time duration (1, 2, 3 and 4 h), on phase formation, grain growth and densification of the mullite ceramics were studied. Characterization techniques used in this project include X-ray diffraction (XRD) and scanning electron microscopy (SEM). Densities of the samples were calculated by using the measured dimension and mass.